SISTEM INFORMASI PENJUALAN IKAN ASIN PADA NIPAH PANJANG BERBASIS WEB: Website;Salted Fish Sales Information System. - Riswan; Wati, Nila (JURNAL AKADEMIKA, 2021)
Sales of Salted Fish in Nipah Panjang is one of the entrepreneurs engaged in selling salted fish that still uses manual systems and the development of systems that are more complicated and far from efficient. One of them is Salin Fish Sales information system in Nipah Panjang which is now not computerized and well integrated, so that it still has many shortcomings in handling sales issues. The approach used in research is the OOAD (Object Oriented Analysis Design) approach and with the Prototype model. To design a new system and so that the design of this new system can overcome the weaknesses of the old system, it must be known how the inputs, processes, and outputs that exist in the current system. The tools used are Data Flow Diagram Modeling (DFD) and balsamiq mockups in building website designs. The results of the design of this system are expected to facilitate the sale of Salted Fish in Long Nipah for the process of selling salted fish and provide information on the price of salted fish in detail.